Preparation method and application of charcoal semicoke-based catalyst

By doping Al and Ca species in the biochar semicoal-based catalyst and combining with the membrane reactor, the problems arising from tar and ash particles during the pyrolysis and gasification process of biomass are solved, and efficient reforming of tar and high-quality gas generation are achieved.

CN119608141AActive Publication Date: 2025-03-14NANJING TECH UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411485755.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-03-14
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

In the prior art, tar and ash slag particles are generated during the pyrolysis and gasification process of biomass waste, resulting in a decrease in gasification efficiency and gas production quality, and may cause equipment corrosion and pipeline blockage, affecting the stable operation of the gasification system.

Method used

Using biochar semicoal-based catalyst, by doping Al and Ca species on the activated carbon catalyst, tar reforming treatment is carried out in combination with a membrane reactor to achieve efficient reforming of tar and high-quality gas generation.

Benefits of technology

The decomposition effect of light compounds in tar reforming is significantly improved, the peak strength of naphthalene, biphenyl and acenaphthalene is reduced, the gas yield and H2/CO ratio are increased, and the in-situ reforming and interception of tar and solid particles is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608141A_ABST
    Figure CN119608141A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a biochar semi-coke-based catalyst, which is characterized by comprising the following preparation steps: S1, preparing biomass semi-coke; and S2, carrying out activating treatment on the prepared biomass semi-coke to obtain the activated charcoal semi-coke-based catalyst. The biomass semi-coke contains natural Ca and Al species which can have a synergistic effect with the charcoal carrier, the porous charcoal is used for cracking macromolecular substances with three rings or more in the tar, and the metal species are used for cracking micromolecular volatile fragments with two rings or less in the tar, so that the tar reforming is promoted, and the hydrogen yield is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tar reforming, and specifically relates to a preparation method and application of a biochar semi-coke-based catalyst. Background Art

[0002] Biomass waste is the largest and most abundant renewable resource on earth. Using pyrolysis and gasification technology to convert biomass waste into clean gas and then prepare chemicals, fuels or energy utilization is an important way to realize the development and utilization of biomass waste according to local conditions. However, tar and ash particles are the main by-products of the pyrolysis and gasification process of biomass waste. The production of tar and ash particles reduces the gasification efficiency and the quality of gas production. Ash particles and sticky tar will cause equipment corrosion and pipeline blockage, which will damage the stable operation of the gasification system and become a bottleneck problem for the promotion and application of gasification technology. Purifying syngas and developing various catalysts to achieve efficient reforming of tar have become current research hotspots. Biomass semi-coke has the characteristics of developed pore structure, low price, and can be directly prepared "in situ" using biomass raw materials. Therefore, biomass semi-coke-based catalysts have gradually become an important application and research topic in the field of tar reforming.

[0003] At present, commonly used tar catalysts include natural catalysts (such as dolomite, olivine), inorganic salt catalysts (such as alkali metals, metal oxides), and synthetic catalysts (such as nickel-based, semi-coke-based metal catalysts). Compared with molecular sieve catalysts and precious metal catalysts, semi-coke-based catalysts are cheap and easy to obtain, have abundant specific surface area, are rich in micropores and mesopores, and during use, new micropores are generated in situ due to the reaction between carbon and tar volatiles, effectively avoiding catalyst deactivation caused by carbon deposition. In previous studies, Tian et al. [1] found that at 700 °C, the conversion rates of toluene on biochar catalysts doped with Co-Ni and Co-Fe reached 97% and 85.3%, respectively. G. Yang et al. [2] found that at 800 °C, the biochar catalyst doped with Ca achieved a tar conversion rate of 70%. In addition, Zhang et al. [3] found that when pine wood was gasified at 750 °C, the tar conversion rate increased from 73.1% to 92.6% using an activated 10wt% Ni-loaded biochar catalyst compared to an unactivated catalyst. In addition, patent CN 106590705A discloses a method for secondary catalytic reforming of tar using an in-situ hot composite semi-coke prepared by pyrolysis of low-quality high-alkali coal and biomass as a catalyst. After adding the composite semi-coke catalyst, the tar yield decreased by about 40%. Patent CN 109876788A involves a method for biomass activated semi-coke catalyst, which is simple, easy to operate, and low in cost. The resulting catalyst exhibits good catalytic activity (~80%) for the tar model compound naphthalene. The above catalysts are prepared from coal or biomass, but do not involve directional regulation of the microstructure and active sites of carbon materials.

[0004] In recent years, the application of bifunctional catalysts with calcium oxide and calcium aluminum as carriers in biomass tar reforming hydrogen production has received more and more attention. They can absorb carbon dioxide produced in the hydrogen production process and have a good catalytic effect. Patent CN 109621936A discloses a CaO-biochar deoxygenation catalyst, which is prepared by rapid pyrolysis of Ca salt and organic materials under an inert gas atmosphere. At 550 ° C, soybean oil WHSV = 2 h -1Under the conditions, the oil and fat compounds are catalytically upgraded to collect high-quality liquid fuel. Patent CN 112473680A relates to a bifunctional calcium-based catalyst, which adopts the calcination-hydration method to prepare the calcium aluminum catalyst carrier, and then adopts the hydrothermal method to load the metal active component. The catalyst catalyzes the production of hydrogen while absorbing CO2 gas, which further promotes the generation of H2. In addition, patent CN 116328772A discloses a Ni-Ca-Al catalyst for coal tar reforming hydrogen production. The catalyst uses NiO as the active component and Al2O3 after chemical activation as the carrier. It contains rich oxygen vacancies, provides active sites for the anchoring of NiO, and increases the synergistic effect of NiO and Al2O3 carrier. In addition, the addition of Ca can further promote the formation of oxygen vacancies, improve the dispersibility of NiO, and significantly improve the activity and stability of the catalyst. Patent CN 115254126A proposes a highly efficient biochar-based Fe-Ni-Ca composite catalyst for treating alkali and alkaline earth metals (AAEM) in biomass pyrolysis volatiles. At the same time, the catalyst can also promote the cracking of biomass pyrolysis tar and maintain an activity similar to that of a fresh catalyst.

[0005] [1] B. Tian, ​​S. Mao, F. Guo, J. Bai, R. Shu, L. Qian, Q. Liu, Monolithic biochar-supported cobalt-based catalysts with high-activity and superior-stability for biomass tar reforming, Energy, 242 (2022) 122970.

[0006] [2] G. Yang, Q. Hu, J. Hu, H. Yang, S. Yan, Y. Chen, X. Wang, H.Chen, Hydrogen-rich syngas production from biomass gasification using biochar-based nanocatalysts, Bioresour. Technol., (2023) 129005.

[0007] [3] Z. Miao, F. Guifang, L. Na, Y. Mingde, L. Xiaoxian, W. Yulong, Tar removal in pine pyrolysis catalyzed by bio-char supported nickelcatalyst, J. Anal. Appl. Pyrolysis, 169 (2023) 105843. Summary of the invention

[0008] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a biochar semi-coke-based catalyst and its application. The natural Ca and Al species contained in the biomass semi-coke can have a synergistic effect with the biochar carrier, which can promote tar reforming; doping Al species on the activated carbon catalyst can significantly decompose light compounds in tar reforming, and the peak intensity of naphthalene, biphenyl and acenaphthylene is significantly reduced after using the Al / activated carbon catalyst; doping Ca species on the activated carbon catalyst can significantly increase the gas yield and H2 / CO ratio in tar reforming.

[0009] In order to achieve the above object, the present invention adopts the following technical solution: A method for preparing a biochar semi-coke-based catalyst comprises the following preparation steps: S1. preparing biomass semi-coke; S2. Activate the prepared biomass semi-coke to obtain an activated biochar semi-coke-based catalyst.

[0010] Preferably, in the aforementioned step S1, the specific preparation steps are: placing a biomass raw material into a reactor, heating it in nitrogen for pyrolysis, and obtaining biomass semi-coke; the biomass raw material is corn cob or poplar wood, with a diameter of 0.3~0.9 mm, a nitrogen flow rate of 50~500 mL / min, a heating rate of 10~50 ℃ / min, heating to 450~550 ℃, and a pyrolysis time of 0.5~2h.

[0011] Preferably, in the aforementioned step S2, the activation treatment method adopts steam activation, the steam heating rate is 5~15 ℃ / min, heated to 750~850 ℃, maintained for 0.5~2 h, the mass ratio of steam to biochar is 0~0.9, and the total flow rate of steam and N2 is 450~550 mL / min.

[0012] Application of a biochar semi-coke-based catalyst in tar reforming.

[0013] A method for improving the decomposition effect of light compounds in tar reforming, using an Al-doped activated carbon catalyst to reform tar, wherein the light compounds are one or more of naphthalene, biphenyl or acenaphthylene.

[0014] Preferably, the method of doping Al on the aforementioned activated carbon catalyst is: using an impregnation / hydrothermal synthesis method, adding the activated carbon catalyst and aluminum salt into deionized water, mixing and stirring, drying, and calcining under nitrogen to obtain an Al / activated carbon catalyst, wherein the aluminum salt is aluminum nitrate or aluminum acetate.

[0015] A method for improving the gas yield and H2 / CO ratio of tar reforming uses a Ca-doped activated carbon catalyst for tar reforming.

[0016] Preferably, the method of doping Ca on the aforementioned activated carbon catalyst is: using an impregnation / hydrothermal synthesis method, adding the activated carbon catalyst and calcium salt into deionized water, mixing and stirring, drying, and calcining under nitrogen to obtain a Ca / activated carbon catalyst, wherein the calcium salt is calcium nitrate or calcium acetate.

[0017] A tar reforming method for simultaneously improving the reforming and interception effects of tar and fixed particles, wherein a membrane reactor is coupled with an activated biochar semi-coke-based catalyst to carry out tar reforming treatment; the membrane reactor is a tubular membrane reactor, which adopts a SiC porous membrane, and the above-mentioned catalyst is filled on the internal channel or the outer wall.

[0018] When the diameter of the tar molecule is 0.65-0.75 nm, the tubular membrane reactor uses a porous membrane with a pore size of 2.5-2.8 μm, and the pore size of the catalyst is 2.8-3.4 nm.

[0019] The present invention is beneficial in that: (1) The natural Ca and Al species contained in the biomass semi-coke of the present invention can have a synergistic effect with the biochar carrier, wherein the porous biochar is used to crack the macromolecular substances with 3 rings or more in the tar, and the metal species are used to crack the small molecular volatile fragments with 2 rings or less in the tar, thereby promoting tar reforming and increasing the hydrogen yield; (2) The present invention can significantly decompose light compounds in tar reforming by doping Al species on the activated carbon catalyst, and the peak intensity of naphthalene and biphenyl / acenaphthylene is significantly reduced after using the Al / activated carbon catalyst; by doping Ca species on the activated carbon catalyst, the gas yield and H2 / CO ratio in tar reforming can be significantly increased; (3) The present invention couples the membrane reactor with the tar reforming catalyst, thereby being able to reform and intercept tar and solid particles in situ in one step, and there is a strong synergistic effect between the catalyst and the membrane; (4) The present invention adjusts the mass ratio of the activator to the biomass semi-coke to directionally adjust the ash content, the specific surface area of ​​the porous carbon and the average pore size, thereby achieving the directional and efficient removal of tar molecules with different molecular diameters. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 : is a diagram of the SiC membrane-gasification system of the present invention: (a) a physical picture of the SiC membrane, (b) a quartz tube reactor based on the membrane, (c) a carbon-based catalyst placed inside or outside the membrane, and (d) a physical picture of the metal filter lining; Figure 2 The XRD and XPS analysis diagrams of different catalysts: (a) XRD local enlarged diagram of different catalysts, (b) XRD overall diagram of different catalysts, (c) XPS analysis of Ca element in biochar, (d) XPS analysis of Ca element in A-Biochar; Figure 3 The effect of catalysts on product distribution: (a) the effect on tar yield and tar removal rate, (b) the effect on synthesis gas yield and H2 / CO, (c) the effect on solid particle yield and solid particle retention rate, (d) SEM image and particle size analysis of solid particles, (e) the effect of activated carbon-based catalyst series on tar yield and tar removal rate, (f) the effect of activated carbon-based catalyst series on synthesis gas yield and H2 / CO; Figure 4 are GC-MS analysis graphs: (a) no catalyst and semi-coke-based catalyst, (b) activated carbon-based series catalysts; Figure 5 The results of TGA-MS are as follows: phenol (m / z=94) (a-a'), indene (m / z=116) (b-b'), naphthalene (m / z=128) (c-c'), biphenyl / acenaphthylene (m / z=154) (d-d'), fluorene (m / z=166) (e-e') and anthracene / phenanthrene (m / z=178) (f-f'); Figure 6 They are: (a) tar yield and tar conversion efficiency diagram of M2.6μm SiC membrane with and without catalyst, (b) particle yield and particle removal efficiency diagram; Figure 7 This is a graph showing the influence of the average pore size of SiC membrane and catalyst, and the diameter of tar molecules on the tar removal rate. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. Example

[0022] In this embodiment, corn cob was used as raw material, corn cob semi-coke was prepared by pyrolysis, and an activated semi-coke-based catalyst was prepared by a physical activation method, which includes the following specific preparation steps: S1. Preparation of biomass semi-coke: The biomass raw materials corn cob or poplar wood (0.3-0.9 mm) were placed in a quartz tube reactor (inner diameter: 25 mm, length: 750 mm) and pyrolyzed for 1 h at a temperature of 500 °C and a heating rate of 30 °C / min in an inert atmosphere of nitrogen (N2, flow rate 400 mL / min) to obtain a biochar semi-coke-based catalyst.

[0023] S2. Activation treatment: About 15 g of biomass semi-coke was loaded into the middle of a quartz tube reactor (length 750 mm, inner diameter 25 mm), heated to 800 °C at a heating rate of 10 °C / min, and maintained at the terminal temperature for 1 h. The corresponding water vapor to biochar (S / B) mass ratio was 0.9, and the total flow rate of the gas mixture (steam / N2) was fixed at 500 mL / min to obtain an activated biochar-based tar reforming catalyst.

[0024] Using activated carbon catalyst as carrier, Al single metal catalyst is prepared by impregnation method / hydrothermal synthesis method, including the following specific preparation steps: The activated carbon catalyst and aluminum nitrate Al(NO3)3 (Al2O3: 10-15 wt%) were mixed and stirred in a beaker containing 50 mL of deionized water for 6 hours; dried at 80 °C for 12 hours, calcined at 800 °C for 1 hour in an inert atmosphere or nitrogen (N2) to obtain an Al / activated carbon catalyst. Alternatively, the activated carbon catalyst and aluminum nitrate Al(NO3)3 were mixed evenly in a beaker containing 50 mL of deionized water, loaded into a kettle, hydrothermally synthesized at 180 °C for 12 hours, dried at 80 °C for 12 hours, calcined at 800 °C for 1 hour in an inert atmosphere or nitrogen (N2) to obtain an Al / activated carbon catalyst.

[0025] The Ca single metal catalyst is prepared by using an activated carbon catalyst as a carrier and an impregnation method / hydrothermal synthesis method, including the following specific preparation steps: The activated carbon catalyst and calcium nitrate Ca(NO3)2 (10-15 wt%) were mixed and stirred in a beaker containing 50 mL of deionized water for 6 hours; dried at 80 °C for 12 hours, and calcined at 800 °C for 1 hour in an inert atmosphere or nitrogen (N2) to obtain a Ca / activated carbon catalyst. Alternatively, the activated carbon catalyst and aluminum nitrate Al(NO3)3 were mixed evenly in a beaker containing 50 mL of deionized water, loaded into a kettle, hydrothermally synthesized at 180 °C for 12 hours, dried at 80 °C for 12 hours, and calcined at 800 °C for 1 hour in an inert atmosphere or nitrogen (N2) to obtain a Ca / activated carbon catalyst.

[0026] Performance test 1. Biochar-based catalyst gasification experiment Gasification experiments were carried out in a membrane-based quartz tube reactor ( Figure 1 (b)), the membrane (length 100 mm, outer diameter 36 mm, inner diameter 24 mm, bottom seal) was connected to a stainless steel tube via a sealing flange with a graphite gasket to ensure that all volatiles were discharged through the membrane before or after interacting with the carbon-based catalyst (e.g. Figure 1 For comparison, a porous stainless steel filter with a diameter of approximately 3 mm and no solid particle filtering capability was used ( Figure 1 (d)), which can be regarded as a fixed bed reactor. For each test, 3 g of biomass was added to the reactor after preheating the reactor to the specified temperature (800 °C). At the same time, water vapor was injected into the reactor through a liquid injection pump water vapor generator, and the mass ratio of water vapor to biomass (S / B) was 1.5. The flow rate of the carrier gas (N2) was 500 mL / min, corresponding to a retention time of volatiles of 29 s. During the gasification process, the solid particles (PMs) in the volatile matter were retained by the silicon carbide (SiC) membrane, while the tar volatile matter was cracked / reformed by the carbon-based catalyst. The liquid product was collected by a sprayer filled with tetrahydrofuran (THF), and the PMs and bio-tar were separated by filtration and rotary evaporation in turn. The non-condensable gases were collected in a gas bag for subsequent analysis.

[0027] 2. Characterization of properties of activated biochar semi-coke-based catalysts X-ray diffraction (XRD) analysis was performed on different catalysts. Figure 2 As shown in (a), the overall pattern is Figure 2(b). In the XRD patterns of Biochar, A-Biochar, ACcomm and Ca / ACcomm catalysts, broad peaks at 2θ of 20-40° were observed, which confirmed the amorphous nature of the carbonaceous materials. Peaks at 2θ of 20.86°, 26.64°, 36.55°, 50.14° and 59.96° were found in all catalysts, which can be classified as (100), (011), (110), (112) and (211) crystal planes of SiO2 (PDF 79-1906).

[0028] In A-Biochar and Ca / ACcomm catalysts, peaks at 31.60°, 33.15°, 41.383° and 44.161° 2θ were observed, corresponding to the (103), (112), (200) and (161) crystal planes of Al4Ca (PDF 14-0428) species, which were absent in Biochar and ACcomm catalysts. In addition, peaks at 31.23°, 31.65° and 39.38° can be classified as the (111), (013) and (113) crystal planes of SiCa (PDF 26-0324) species, which were observed in A-Biochar and Ca / ACcomm catalysts, but absent in Biochar and ACcomm catalysts.

[0029] The Ca-containing peaks observed in A-Biochar indicate that metal active sites are better exposed on the carbonaceous matrix during activation, which should facilitate the interaction between biovolatiles and the catalyst. This result is confirmed by the presence of Ca-containing peaks in the biochar and A-Biochar catalysts ( Figure 2 The XPS surface analysis of (c)-(d)) further supports that the peak intensity of Ca2p scanning pattern of A-Biochar is higher than that of Biochar. 3 / 2 and Ca2p 1 / 2 The peaks are located at binding energies of approximately 346.8 eV and 250.4 eV, respectively.

[0030] The porosity analysis results of different catalysts are summarized in Table 1. As the benchmark catalyst, the surface area of ​​ACcomm catalyst is about 672.6 m² / g, the micropore area is 491.1 m² / g, the surface area of ​​Biochar is 208.7 m² / g, and when the semi-coke is activated under the condition of steam to semi-coke mass ratio of 0.5, the surface area increases to about 324.4 m² / g, and the pore size also increases from 2.4 nm of Biochar to 3.1 nm of A-Biochar. Unless otherwise specified in the present invention, the catalyst obtained under the condition of steam to semi-coke mass ratio of 0.5 is tested. During the catalytic gasification of biomass, larger volatile fragments can be cracked into smaller fragments in the mesoporous structure of the catalyst, and they can be further cracked by micropores when they pass through the catalyst bed. This hierarchical pore effect of the A-Biochar catalyst is beneficial for the reforming / cracking of bio-tar to produce clean syngas. During the activation process, the mass ratios of water vapor to semi-coke were 0.3, 0.5, and 0.7, respectively. The properties of the prepared catalysts are shown in Table 1.

[0031] Table 1 Properties of different catalysts

[0032] in: a BET surface area, b t-Plot Micropore area, c The total pore volume of single-point adsorption for pores with diameters less than 808 nm at p / p° = 1, d t-Plot Micropore Volume, e 4V / A by BET method.

[0033] 3. Effect of catalyst on product distribution like Figure 3 As shown in (a), in the SiC film ( Figure 1 In (c)), the tar conversion increased from about 48.9% without catalyst to about 81.6%. These results were accompanied by an increase in syngas production (about 66 mmol / gbiomass, Figure 3 (b)) and the improvement of PM removal efficiency (89%, Figure 3 The surface area of ​​the biochar was increased from 208.7 m to 1.3 m by steam activation at 800 °C with a steam to char mass ratio of 0.3. 2 / g increased to 333.5 m 2 / g, and further increasing the steam to biochar mass ratio to 0.5, 0.7, and 0.9 resulted in a slight decrease in surface area and a slight increase in total volume and average pore size (Table 1). The highest tar conversion of about 86.1% was achieved at a steam to biochar mass ratio of 0.5 (tar yield of 13.8 g / m 3 ). At the same time, the syngas yield and PM removal efficiency increased to 74 mmol / g biomass (H2 / CO ratio of about 2.1) and 94.5%, respectively. Thereafter, the optimal A-Biochar activated at a steam to biochar mass ratio of 0.5 was used. In addition, Figure 4 GC-MS spectra in (a) and Figure 5 The TGA-MS patterns in Figure 2 confirm the superiority of the activated char catalyst over the unactivated char catalyst in tar cracking / reforming. This strong beneficial effect of catalyst activation on tar cracking / reforming reactions and syngas quality improvement should be attributed to the higher ash-forming mineral content (48.2% for A-Biochar and 22.3% for Biochar, Table 2), higher specific surface area (324.4 m for A-Biochar), and the higher ash-forming mineral content (48.2% for A-Biochar and 22.3% for Biochar, Table 2). 2 / g, relative to Biochar is 208.7m 2 / g), and better exposure of metal species (especially Ca).

[0034] Table 2 Organic analysis, industrial analysis and ash composition of different catalysts

[0035] in: a ad: dry basis, b daf: water-free and ash-free basis, c Difference.

[0036] Since the location of the catalyst inside or outside the membrane also affects the tar conversion efficiency by adjusting the secondary reactions of volatiles, the catalytic performance was additionally evaluated when the A-Biochar catalyst was loaded outside the membrane. It was found that the tar conversion efficiency was significantly improved to about 96.4%, and the H2 / CO ratio was increased to 2.4. At the same time, the removal rate of inhalable particulate matter was also improved to about 95.9% by loading the A-Biochar catalyst outside the membrane. This indicates that the catalyst helps the cracking and steam reforming reactions of heavy volatiles, thereby reducing the formation of coke deposits in inhalable particulate matter.

[0037] To elucidate the role of active metals in the porous carbon matrix and biochar, four catalysts were prepared, including ACcomm (a commercial activated carbon catalyst) and ACcomm catalyst doped with the same amount of Ca, Al, and Ca / Al as the A-Biochar catalyst. The ACcomm catalyst was used as a control catalyst, which has a lower ash content (~13.4%) and a much larger specific surface area (672.6 m 2 / g). The tar conversion efficiency and gas yield of the ACcomm catalyst were approximately 94.3% and 58mmol / g biomass, respectively, which were lower than those of the A-Biochar catalyst, indicating that metal species (Ca and Al with the highest content) played an important role in the A-Biochar catalyst. In addition, the inhalable particulate matter removal efficiency of the ACcomm catalyst was similar to that of the A-Biochar catalyst, or even slightly lower than that of the A-Biochar catalyst. This indicates that the porous structure of the carbon matrix of the A-Biochar and ACcomm catalysts has a positive effect on the interception of inhalable particulate matter, which is attributed to the strong cracking effect of the porous structure on heavy volatile substances.

[0038] The pyrolysis effect of the porous carbon matrix was shown by the almost colorless tar obtained using A-Biochar and ACcomm series catalysts and the GC-MS spectra ( Figure 4 The absence of heavy compound peaks in the TGA-MS mode was further confirmed by the absence of heavy compound peaks in the TGA-MS mode. Figure 5 of (b-b')), naphthalene (128) ( Figure 5 of (c-c')) and biphenyl / acenaphthylene (154) ( Figure 5 Compared with the (d-d')), after using A-Biochar catalyst, fluorene (166) ( Figure 5 of (e-e') and anthracene / phenanthrene (178) ( Figure 5 The signal of (f-f') was significantly reduced or even undetectable after using ACcomm catalyst, which suggested the superior effect of porous matrix on the cracking reaction of heavy compounds.

[0039] Regarding the role of metal species, it was found that doping of Ca, Al, and Ca / Al species on ACcomm catalysts had little effect on PMs yield and only slightly increased tar conversion from about 94% for ACcomm catalysts to 95%-96% for Al-doped, Ca-doped, and / or Ca / Al-doped catalysts ( Figure 3However, the gas yield and H2 / CO ratio increased significantly from 58 mmol / g biomass (H2 / CO about 1.50) for the ACcomm catalyst to about 70 mmol / g biomass (H2 / CO about 2.4) for the Al / ACcomm catalyst and about 79 mmol / g biomass (H2 / CO about 2.4) for the Ca / ACcomm catalyst ( Figure 3 (f)). Figure 4 (b) shows that the decomposition of light compounds (1-2 rings, such as naphthalene) is significant after doping with Al species on the ACcomm catalyst, while it is almost undetectable after doping with Ca species. Similar results were also found in TGA-MS analysis. The peak intensities of naphthalene (m / z=128) and biphenyl / acenaphthylene (m / z=154) are significantly reduced after using ACcomm catalysts doped with Ca and Al species ( Figure 5 These results indicate that Ca and Al in the A-Biochar catalyst should be the main active species for the cracking and reforming of relatively light tar fragments (e.g., 1-2 ring compounds) to generate gas, and that Ca species is slightly superior to Al species in improving gas yield and H2 / CO ratio ( Figure 3 The superior effect of Ca should be attributed to the higher basicity of Ca / ACcomm (1.67 mmol / g) relative to 1.08 mmol / g of Al / ACcomm, which was confirmed by the CO2-TPD test results.

[0040] The above results show that doping Al species on ACcomm catalyst can effectively crack naphthalene, biphenyl or acenaphthylene. In addition, doping Ca species on ACcomm catalyst can not only effectively crack naphthalene, biphenyl or acenaphthylene, but also significantly improve the tar reforming gas yield and H2 / CO ratio.

[0041] 4. Synergy between catalyst and membrane reactor During the experiment, the mass ratio of carbon-based catalyst to biomass was 1:1.5, and the filling method of carbon-based catalyst was as follows Figure 1 The membrane reactor is filled as shown in (c) to ensure that all volatiles are discharged through the membrane before or after interacting with the carbon-based catalyst. By coupling the membrane reactor with a tar reforming catalyst, tar and solid particles can be reformed and retained in situ at the same time, and there is a strong synergistic effect between the catalyst and the membrane. Different catalysts were coupled to the membrane reactor for tar reforming, and the reforming and retention effects of tar and solid particles, as well as the gas yield and H2 / CO ratio were compared. The specific results are shown in Tables 3 and 4.

[0042] Table 3 Reforming and interception of tar and solid particles after coupling different catalysts with membrane reactors

[0043] According to Table 3 and Figure 6 It can be seen that, taking the 2 μm silicon carbide membrane and A-Biochar catalyst as an example, when there is no catalyst, the membrane can only retain 48.94% and 56.16% of tar and solids. When there is only a catalyst, the catalyst can only reform 71.23% and 9.59% of tar and solid particles. However, when the two are coupled, the reforming effect on tar can reach 96.36%, and at the same time, the retention effect on solid particles can reach 95.89%. It can be seen that coupling the membrane reactor with the tar reforming catalyst can simultaneously improve the in-situ reforming and retention of tar and solid particles.

[0044] Table 4 Gas yield and H2 / CO ratio of tar reforming after coupling different catalysts with membrane reactor

[0045] It can be seen from Table 4 that when there is no catalyst, the H2 / CO ratio of the membrane in the tar reforming process is 1.06, and when only the A-Biochar catalyst is present, the H2 / CO ratio of the A-Biochar catalyst in the tar reforming process is 1.64. However, when the membrane is coupled with the A-Biochar catalyst, the H2 / CO ratio can reach 2.35, and the gas yields of CO2 and CH4 are also higher than those of only the membrane or only the A-Biochar catalyst. It can be seen that after the membrane is coupled with the A-Biochar catalyst. In addition, after the membrane is coupled with the Ca / ACcomm catalyst, the H2 / CO ratio is the highest, up to 2.43, and the gas yields of CO2 and CH4 are also significantly increased. This proves that doping Ca species on the ACcomm catalyst can significantly increase the tar reforming gas yield and H2 / CO ratio.

[0046] In addition, if Figure 7 As shown in the figure, by studying the influence of membrane pore size and catalyst average pore size on the tar removal rate of different molecular kinetic diameters, it can be seen that the smaller the SiC membrane pore size (2.6 μm-50 μm), the better the cracking effect of tar molecules with smaller molecular diameters. When the membrane pore size is 2.6 μm, the removal rate of tar molecules with a molecular diameter of 0.69 nm is the highest, about 70%. However, the effect of the catalyst average pore size on the tar removal rate of different molecular diameters is more complicated. When the catalyst average pore size is 3.1 nm, the tar removal effect is the best, with a removal rate of about 96%.

[0047] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing a biochar semi-coke-based catalyst, characterized in that: The method comprises the following preparation steps: S1, preparing biomass semi-coke; S2. Activate the prepared biomass semi-coke to obtain an activated biochar semi-coke-based catalyst.

2. The method for preparing a biochar semi-coke-based catalyst according to claim 1, characterized in that: In the step S1, the specific preparation steps are: putting the biomass raw material into the reactor, heating it in nitrogen for pyrolysis, and obtaining biomass semi-coke; the biomass raw material is corn cob or poplar wood, with a diameter of 0.3-0.9 mm, a nitrogen flow rate of 50-500 mL / min, a heating rate of 10-50 °C / min, heating to 450-550 °C, and a pyrolysis time of 0.5-2 h.

3. The method for preparing a biochar semi-coke-based catalyst according to claim 1, characterized in that: In step S2, the activation treatment method adopts water vapor activation, the steam heating rate is 5-15 ° C / min, heated to 750-850 ° C, maintained for 0.5-2 h, the mass ratio of steam to biochar is 0-0.9, and the total flow rate of steam and N2 is 450-550 mL / min.

4. Use of a biochar semi-coke-based catalyst as claimed in claim 1 in tar reforming.

5. A method for improving the decomposition effect of light compounds in tar reforming, characterized in that: Tar reforming is carried out using an Al-doped activated carbon catalyst, wherein the light compound is one or more of naphthalene, biphenyl or acenaphthylene.

6. The method for improving the decomposition effect of light compounds in tar reforming according to claim 5, characterized in that: The method of doping Al on the activated carbon catalyst is: using an impregnation / hydrothermal synthesis method, adding the activated carbon catalyst and aluminum salt into deionized water, mixing and stirring, drying, and calcining under nitrogen to obtain an Al / activated carbon catalyst, wherein the aluminum salt is aluminum nitrate or aluminum acetate.

7. A method for increasing the yield of tar reforming gas and the H2 / CO ratio, characterized in that: Tar reforming using Ca-doped activated carbon catalyst.

8. The method for improving the tar reforming gas yield and H2 / CO ratio according to claim 7, characterized in that: The method for doping Ca on the activated carbon catalyst is: using an impregnation / hydrothermal synthesis method, adding the activated carbon catalyst and calcium salt into deionized water, mixing and stirring, drying, and calcining under nitrogen to obtain a Ca / activated carbon catalyst, wherein the calcium salt is calcium nitrate or calcium acetate.

9. A tar reforming method for simultaneously improving the reforming and interception of tar and fixed particles, characterized in that: Tar reforming treatment is carried out by coupling a membrane reactor with the activated biochar semi-coke-based catalyst prepared in claims 1 to 3; the membrane reactor is a tubular membrane reactor, using a SiC porous membrane, and the activated biochar semi-coke-based catalyst is filled on the internal channel or outer wall of the tubular membrane reactor.

10. The tar reforming method for improving the reforming and interception of tar and fixed particles according to claim 9, characterized in that: When the diameter of tar molecules is 0.65-0.75 nm, the tubular membrane reactor uses a SiC porous membrane with a pore size of 2.5-2.8 μm, and the pore size of the catalyst is 2.8-3.4 nm.

Citation Information

Patent Citations

  • Method for secondarily reforming tar by utilizing in-situ composite semicoke made from high alkaline coal and biomass

    CN106590705A

  • CaO-charcoal deoxidization catalyst and method for catalyzing a grease-type compound to prepare liquid fuel

    CN109621936A

  • Bifunctional calcium-based catalyst and preparation method and application thereof

    CN112473680A

  • Preparation method of biochar-based bifunctional catalyst

    CN115254126A

  • Load type nickel base doped catalyst for biomass tar splitting and preparation method thereof

    CN102151569A